2014
DOI: 10.1021/jp507272f
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Transient Absorption Spectroscopy of the Medicinal Agent Curcumin in Diamide Linked γ-Cyclodextrin Dimers

Abstract: Curcumin is a biologically active polyphenol and a yellow pigment extracted from turmeric. Our previous study has shown effective encapsulation of curcumin using diamide linked γ-cyclodextrin dimers, namely 66γCD2su and 66γCD2ur, through cooperative 1:1 host-guest complexation. In this study, the excited-state dynamics of curcumin complexed with either 66γCD2su or 66γCD2ur in water are investigated using femtosecond transient absorption spectroscopy. Both 66γCD2su-curcumin and 66γCD2ur-curcumin complexes in wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…The presence of a deuterium isotope effect is consistent with the assignment of this major relaxation process of curcumin in the PAAC18 hydrogel to ESIHT. As established in previous studies, [42][43][44][45][46][47][48] ESIHT is an important photophysical process of excited-state curcumin. It was also shown that the interactions between the enolic hydrogen of curcumin and polar solvent molecules influence the rate of ESIHT.…”
Section: Femtosecond Transient Absorption and Excited-state Dynamics ...mentioning
confidence: 57%
See 3 more Smart Citations
“…The presence of a deuterium isotope effect is consistent with the assignment of this major relaxation process of curcumin in the PAAC18 hydrogel to ESIHT. As established in previous studies, [42][43][44][45][46][47][48] ESIHT is an important photophysical process of excited-state curcumin. It was also shown that the interactions between the enolic hydrogen of curcumin and polar solvent molecules influence the rate of ESIHT.…”
Section: Femtosecond Transient Absorption and Excited-state Dynamics ...mentioning
confidence: 57%
“…It was also shown that the interactions between the enolic hydrogen of curcumin and polar solvent molecules influence the rate of ESIHT. [43][44][45][46][47][48] Curcumin in the PAAC18 hydrogel exhibits a relatively fast ESIHT process compared with curcumin in protic solvents, 42,43,[46][47][48] consistent with the presence of water in the PAAC18 hydrogel. The deuterium isotope effect of 1.7 of curcumin in the PAAC18 hydrogel is identical to that of curcumin in methanol, similar to those observed in micelles (1.6) but lower than that in ethylene glycol (2.1).…”
Section: Femtosecond Transient Absorption and Excited-state Dynamics ...mentioning
confidence: 92%
See 2 more Smart Citations
“…Curcumin ( Cu ), as one of the active components of Indian turmeric, has exhibited potential applications as therapeutic agents against several diseases because of its low toxicity, good anti-inflammatory and antibacterial capabilities, and anticancer activities. However, the low solubility and fast degradation assigned to physiological pH and photoinduced instability in aqueous media restrained numerous applications of curcumin in therapeutic agents and photodynamic inactivation ( PDI ) against cancerous cells and pathogenic microorganisms. In addition, the equilibrium corresponding to keto- and enol-tautomers, ultrafast excited-state processes closely associated with salvation, and excited-state intramolecular hydrogen atom transfer ( ESIHT ) have been considered important factors affecting its antibacterial and antioxidant capacities in solution. Thus, surfactant utilization and encapsulation into delivery systems such as conjugates, nanoparticles, molecular complexes, micelles, liposomes, hydrogels, and emulsions have been utilized to improve the solubility, stability, and biocompatibility of curcumin in aqueous media.…”
Section: Introductionmentioning
confidence: 99%